Perbandingan Hukum Tentang Kedudukan Komisi Pemberantasan Korupsi Sebelum Dan Setelah Perubahan Undang-Undang No 30 Tahun 2002 Tentang Komisi Pemberantasan Korupsi - Jumadil Aravi; Armina Aya Sovya Sy; Nadya Maghfirah; Veoni Sinta Nosi; Putri Maharani; Mesrizal .; Salmi Agustria; Cinta Geovani; Khairani Latita; Muhammad Nazif; Kaka Rollanda; Divo Algusti; Elwidarifa Marwenny (CV. ITTC INDONESIA, 2026)
This study aims to examine the position of the Corruption Eradication Commission (KPK) after the amendment of Law No. 30 of 2002 through Law No. 19 of 2019. The approach used is juridical-empirical using literature studies. Data were collected by compiling journals on the Corruption Eradication Commission (KPK) and related literature. The results of the study indicate that the Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission through Law Number 19 of 2019 is one of the most controversial legislative changes in the history of legal reform in Indonesia. This change has fundamental implications for the position, institutional character, and level of independence of the Corruption Eradication Commission (KPK) as a state institution specifically established to eradicate corruption. This article aims to comprehensively examine the position of the KPK after the enactment of Law Number 19 of 2019 from the perspective of constitutional law and the principles of the rule of law. The research method used is normative legal research with a statutory, conceptual, and historical approach. The results of the study indicate that the change in the position of the KPK as a state institution within the executive branch of power, the establishment of the Supervisory Board, and the change in the status of KPK employees to State Civil Apparatus (ASN) have shifted the paradigm of KPK independence. Although the changes are claimed to be aimed at strengthening accountability and oversight, in practice they have the potential to weaken the effectiveness of the Corruption Eradication Commission (KPK) as an independent institution in eradicating corruption.